The Use of Animated Videos to Increase Learning Motivation for the Material on Renewal Movements in Islam - Hadini Hadini; Weti Susanti; Hayati Hayati; Muksalmina Muksalmina (Institute of Research and Community Service STAI Yayasan Tarbiyah Islamiyah Kota Padang, 2026)
The use of animated video media in education has an influence on increasing learning motivation. Ignoring it can result in a decrease in student motivation in learning. This is due to the lack of student motivation in learning Islamic Cultural History. This is seen as some students do not listen to the material from the teacher, get bored easily, and walk around outside the classroom, with various reasons given. The purpose of this writing is (1) to describe the activities of teachers and students through the use of animated video media, (2) to describe the increase in student learning motivation through the use of animated video media in learning Islamic Cultural History, especially in the material of the Renewal Movement in Islam. This research is a Classroom Action Research (CAR) which consists of 4 stages, namely planning, action, observation, and reflection. The subjects of this research are students of class XI Religion at Madrasah Aliyah Negeri 2 Bireuen. Data collection techniques through (1) teacher activity observation sheets, (2) student activity observation sheets, (3) questionnaires. Based on the results of the research data analysis, it was found that (1) teacher activity in cycle I was 80% in the good category, cycle II increased to 92% in the very good category, while student activity in cycle I was 76% in the good category, in cycle II it increased to 91% in the very good category, (2) the percentage of student learning motivation in cycle I was 84% ​​in the good category, in cycle II the percentage of student learning motivation was 92% in the very good category. So it can be concluded that the use of animated video media can increase student learning motivation in the material of the Renewal Movement in Islam.